DISPERSION OF MCM-41 AND C20 INTO POLYSULFONE MEMBRANE FOR GAS SEPARATION - WONG , YEAN SANG (2018)
Hybrid membrane which consists of inorganic fillers dispersed in polymer matrix, is believed to show promising performance towards separation of gas pairs. However, filler dispersion is one of the major challenges in hybrid membrane fabrication. Poor dispersion and distribution lead to agglomeration of particles. This will affect the gas separation performance as gases tend to permeate through unreinforced polymer regions, causing high permeability and low selectivity gas separation performance. Despite the importance of ensuring uniform dispersion, there is a lack of systematic investigation on the appropriate technique to quantify the degree of dispersion and distribution of nanoparticles in hybrid membranes.